Random grid-based visual secret sharing for general access structures with cheat-preventing ability - Wu, Xiaotian; Sun, Wei (The Journal of systems and software, 2012)
► We propose a RG-based VSS for general access structures. ► Pixel expansion problem is solve in the proposed scheme. ► Complex sharing strategy can be realized by the proposed scheme. ► A cheating immune method is proposed to prevent VSS from being cheated. Conventional visual secret sharing (VSS) encodes a secret image into shares which are m times as big as the secrets. m is called pixel expansion. Random grid (RG) is an approach to solve pixel expansion problem. However, the existing VSS methods using RGs are confined to (2,n),(n,n) and (k,n). In this paper, RG-based VSS schemes for general access structures are proposed. The proposed algorithms can encode one secret image into n random grids while qualified sets can recover the secret visually. Furthermore, a cheating immune method is also presented to provided extra ability of cheat-preventing for RG-based VSS. Experimental results demonstrate that both the RG-based VSS for general access structures and cheating immune method are effective. More complicated sharing strategies can be implemented.